The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12904-018-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Transitions as experienced by persons in palliative care circumstances and their families – a qualitative meta-synthesis

Abstract: BackgroundWhen receiving palliative care, patients and their families experience altered life situations in which they must negotiate challenges in daily life, increased care and new roles. With limited time, they also experience emotional changes that relate to their uncertain future. Transitions experienced in such situations are often studied by focusing on individual aspects, which are synthesized in the following study. The aim was to conduct a qualitative meta-synthesis to explore the experiences patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 38 publications
1
64
0
2
Order By: Relevance
“…In our study, the caregivers talked about how difficult it was to be in the role of an “assistant” instead of the role of a close family member. Studies have reported that changing roles can be difficult for family caregivers involved in palliative care (Fringer et al, ). To handle multiple roles could lead to over‐exertion and these contradictory roles must be balanced (Fringer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the caregivers talked about how difficult it was to be in the role of an “assistant” instead of the role of a close family member. Studies have reported that changing roles can be difficult for family caregivers involved in palliative care (Fringer et al, ). To handle multiple roles could lead to over‐exertion and these contradictory roles must be balanced (Fringer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that changing roles can be difficult for family caregivers involved in palliative care (Fringer et al, ). To handle multiple roles could lead to over‐exertion and these contradictory roles must be balanced (Fringer et al, ). In our study, this need for balance was significant, especially when the patient rejected support offered by healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…End of life care transitions can be practically and emotionally difficult for family members 1 . They signify the certainty of impending death 2 and evoke many uncertainties about the future, including care after discharge 7 . Thus, care transitions are a 'critical time' during which family members need additional support and information 8 and present an opportunity for health and social care professionals to identify and respond to this need.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple systematic reviews have examined the experiences and needs of end-of-life caregivers [3,[5][6][7][8][9][10][11][12]. Although many individual studies are rooted in conceptual or theoretical frameworks [13], few systematic reviews have them as an analytic structure: Broady [8] used personal construct psychology as the basis for framework analysis, and Morgan [10] conducted a feminist quality appraisal of gender in family caregiving.…”
Section: Introductionmentioning
confidence: 99%